Pengaruh Brand Image terhadap Keputusan Pembelian di Restoran Bakmie Kalimantan Hin Lie - Wardanah, Iga Dwi; Paulana, Usmarus (LPPM Institut Nasional Laa Roiba Bogor, 2024)
Most of the consumers who come to the Bakmie Kalimantan Hin Lie Restaurant are consumers who have high trust and a positive view of the brand image in the restaurant. In addition, the Bakmie Kalimantan Hin Lie Restaurant has unique characteristics and advantages which most restaurants do not have. Therefore, this study was conducted to determine the effect of Brand Image in three dimensions, namely the dimensions of Strength, Uniqueness and Favorable on purchasing decisions at Bakmie Kalimantan Hin Lie Restaurant. This study used quantitative methods and data collection techniques were carried out using questionnaires and interviews. Then, the researcher used the Nonprobability Sampling technique with the Purposive Sampling method to determine a research sample. Then the researchers used the Pearson Product Moment formula to measure the validity test and used the Alpha Cronbach technique to measure the reliability test. The analytical method used in this study is a simple linear regression analysis method using the SPSS Version 25 application.Based on the results of data analysis carried out, it is simultaneously proven that there is a positive and significant influence on consumer purchasing decisions at the Bakmie Kalimantan Hin Lie Restaurant, this can be seen from the Strenghtness dimension, the value of tcount on the Strenghtness dimension is 2.302 and the sig value obtained is 0.023, then for the Uniqueness dimension, the tcount value for the Uniqueness dimension is 1,110 and the sig value is 0.270 and the last for the Favorable dimension, the tcount value for the Favorable dimension is 0.390 and the sig value is 0.697. then with the value of Fcount on the Brand Image variable of 5.939 and the sig value of 0.017. Keywords: Brand Image, Purchase Decision, Restaurant